Effectiveness of Dynamic Neuromuscular Stabilization Breathing in Enhancing Spirometry Indices among Sedentary Students with Poor Posture - Binu, David. P.; Poovishnudevi, T. (Journal of Neonatal Surgery, 2025)
Poor posture has become prevalent in modern sedentary lifestyles, significantly impacting musculoskeletal and respiratory functions. Prolonged periods of sitting, inadequate postural habits, and reduced physical activity contribute to musculoskeletal imbalances, which in turn affect respiratory mechanics by restricting thoracic mobility and impairing diaphragmatic function. This study investigates the effect of Dynamic Neuromuscular Stabilization (DNS) breathing exercises on pulmonary function parameters in individuals with postural dysfunction. A cohort of sedentary individuals exhibiting postural impairments participated in a structured DNS intervention program focused on optimizing postural alignment and enhancing diaphragmatic breathing control. Pulmonary function was assessed through spirometry, measuring Maximum Voluntary Ventilation (MVV), Forced Expiratory Volume in the first second (FEV1), and Forced Vital Capacity (FVC) both before and after the intervention. Results demonstrated statistically significant improvements (p < 0.001) across all measured parameters, indicating enhanced respiratory muscle efficiency, increased lung volumes, and improved airflow dynamics following DNS training. These findings highlight the potential of DNS as a rehabilitative approach for enhancing respiratory health in sedentary populations. By addressing postural dysfunction and promoting optimal breathing patterns, DNS can serve as an effective intervention to mitigate the adverse effects of prolonged sedentary behavior on pulmonary function. The study provides strong evidence for the incorporation of DNS techniques into physiotherapy and rehabilitation programs aimed at improving respiratory performance and overall well-being. Further research is warranted to explore the long-term benefits of DNS and its applicability across different populations, including individuals with chronic respiratory conditions and athletes seeking to optimize their breathing efficiency. Aim of the Study The study aims to evaluate the effectiveness of Dynamic Neuromuscular Stabilization (DNS) breathing exercises in enhancing pulmonary function parameters among sedentary students with poor posture. By assessing spirometric indices such as Maximum Voluntary Ventilation (MVV), Forced Expiratory Volume in the first second (FEV1), and Forced Vital Capacity (FVC), the research seeks to determine the impact of DNS on respiratory efficiency and postural alignment. Need for the Study Sedentary lifestyles and poor posture have become increasingly prevalent due to prolonged sitting, leading to musculoskeletal imbalances and compromised respiratory function. Research has highlighted the correlation between postural dysfunction and reduced lung volumes, yet limited studies have explored the role of DNS in addressing these issues. By integrating postural correction with breathing re-education, DNS may offer a novel approach to improving pulmonary function. This study is necessary to establish evidence-based recommendations for DNS as a rehabilitative intervention for individuals experiencing postural-related respiratory inefficiencies. Objectives of the Study To assess the effect of DNS breathing exercises on pulmonary function parameters (MVV, FEV1, and FVC) in sedentary students with poor posture. To compare the effectiveness of DNS breathing exercises with conventional physiotherapy in improving respiratory efficiency. To evaluate the role of postural correction in enhancing respiratory mechanics and lung volumes. To determine the statistical significance of improvements in spirometric indices following DNS intervention. To provide evidence for the incorporation of DNS into physiotherapy and rehabilitation programs aimed at enhancing respiratory function. Methods: A cohort of sedentary individuals exhibiting postural dysfunction participated in a structured DNS program. Pulmonary function was assessed through spirometry, measuring MVV, FEV1, and FVC both pre- and post-intervention. The DNS exercises focused on enhancing diaphragmatic control, spinal stabilization, and overall postural alignment. Results: Statistical analysis revealed significant improvements in all measured variables. MVV exhibited a notable increase, reflecting enhanced respiratory muscle strength and endurance. Similarly, FEV1 and FVC showed significant gains, suggesting improved lung expansion, airway function, and overall pulmonary efficiency. The rise in FEV1/FVC ratio further indicated better airflow regulation and reduced airway resistance. Conclusion: This study underscores the efficacy of DNS in improving pulmonary function parameters among sedentary individuals with poor posture. Our findings align with prior studies emphasizing the crucial relationship between postural control and respiratory efficiency. By addressing the biomechanical and neuromuscular dimensions of respiration, DNS presents a holistic approach to mitigating the adverse effects of sedentary behavior on respiratory health. Future research should explore long-term outcomes and broader applications of DNS in clinical and rehabilitative settings, particularly in populations prone to postural and respiratory dysfunctions due to occupational or lifestyle factors.